PERSEPSI MASYARAKAT TERHADAP RENCANA PENETAPAN KAWASAN RIAM SENGIANG SEBAGAI OBJEK WISATA ALAM DI DESA NANGA KEMPANGAI KABUPATEN MELAWI - Asang, .; Lumangkun, Augustine; Wardenaar, Evy (JURNAL HUTAN LESTARI, 2016)
The Riam (cascade) Sengiang area is the administrative region neighboring Nanga Kempangai Village District of Ella Hillir Melawi. The area is located in the basin of Ella River ,it define the status of the region and needs to be developed into aÂ  natural tourism area. With the establishment plan can provide good benefits to the surrounding community, goverment agencies as well as the environment. Relating to the needs above, this research tried to investigate public perceptions in the Riam Sengiang. The research showed of data analysis showed that the public perception of the plan designation of Riam sengiang as the object for natural tourism in this area have a high perception with 63,33 %, moderate perception with 20.00% and low perception with 16,67 %. This high level of public perception village have awardness the importance things to establish the ecotourism area that has an impact for environment, the community's economy and the lives of their children and grandchildren in the future. Keywords : Public perception, area designation cascade Sengiang